2001
DOI: 10.1128/jcm.39.3.1124-1129.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evolution of the Human Immunodeficiency Virus Type 1 Gag-Protease Region and Maintenance of Reverse Transcriptase Resistance following Prolonged Drug Exposure

Abstract: We studied the human immunodeficiency virus type 1 phenotypic and genotypic profiles of a dual drugresistant isolate (isolate 14aPost-DR) selected for zidovudine (ZDV) and lamivudine (3TC) resistance and then cultured in the presence of 3TC and a protease inhibitor: indinavir (IDV), ritonavir, or KNI-272. The IDV-treated virus was highly resistant to 3TC, ZDV, and IDV and accumulated protease mutations at positions M46I and V82F. A change from alanine to valine was observed in 4 of 10 clones in the P2 position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The NC-p1 cleavage site has been seen to coevolve in response to the V82A drug-resistant mutation in HIV-1 protease, with the Ala residue at P2 mutating to a Val (1,10,20,55). Previous studies on the kinetics of substrate cleavage have shown that this mutation results in the substrate's being nition of the NC-p1 substrate cleavage site, and when the drug-resistant V82A mutation occurs, the interactions at P1 and P1Ј are perturbed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NC-p1 cleavage site has been seen to coevolve in response to the V82A drug-resistant mutation in HIV-1 protease, with the Ala residue at P2 mutating to a Val (1,10,20,55). Previous studies on the kinetics of substrate cleavage have shown that this mutation results in the substrate's being nition of the NC-p1 substrate cleavage site, and when the drug-resistant V82A mutation occurs, the interactions at P1 and P1Ј are perturbed.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that V82A is a prime site for drug resistance to occur, as the valine at residue 82 is not critical for substrate recognition but does extensively contact many of the commonly used inhibitors (39). However, the apparent coevolution of the NC-p1 cleavage site (AP2V) with the V82A mutation in the protease (1,10,20,55) implies that Val82 plays an important role in the protease's recognition of the NC-p1 substrate, a role that is lost when the V82A mutation occurs.…”
Section: Maturation Of Human Immunodeficiency Virus (Hiv) Depends On mentioning
confidence: 99%
See 1 more Smart Citation
“…Such coevolution has occasionally been seen, although it has been primarily limited to the NC-p1 cleavage site. In this case, the P2 residue mutates from an alanine to a valine in the presence of the V82A protease drug-resistant mutation (14,21,46). These results are encouraging in that the virus may have more difficulty in developing resistance to TMC114 than to other protease inhibitors; however, with the heterogeneity of HIV in vivo this will be confirmed only when extensive clinical trials are concluded.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies provided structural insights into why a prime drug-resistant mutation, V82A (5,8,10,31,46), has less effect on substrate binding than on inhibitor binding as Val82 interacts more closely with the drugs than with natural substrates (41). The nucleocapsid-p1 (NC-p1) substrate, however, coevolves (AlaP2Val) in a correlated manner with the V82A mutation (3,6,9,23,56). Processing of the NC-p1 substrate is the slowest and rate-determining cleavage step in the maturation of Gag (38,50,55).…”
mentioning
confidence: 99%